Territorial inequality of food insecurity in households with children and adolescents of Tucumán (Argentina) during the first months the CoVID-19 pandemic - Cordero, Maria Laura (2023)
The CoVID-19 pandemic constitutes a macro-social event that reinforces territorial inequalities. The objective of this study is to increase knowledge of food security in the province of Tucumán during the first months of the CoVID-19 pandemic, by describing the extent and distribution of food insecurity at a departmental level, and analyzing, in particular, households with children and adolescents. A quantitative and cross-sectional study was carried out by means of a digital questionnaire. The Latin American and Caribbean Scale for the measurement of Food Security was applied to distinguish between households with food security and households with food insecurity (mild, moderate, severe). Information from 3,915 households was obtained. Prevalences of food insecurity were calculated at a departmental level and according to the presence or absence of minors in the household. In addition, spatial indicators and thematic cartography were developed and census data were analyzed. Comparisons were made considering the presence of minors in the home (chi-square tests). The results indicated that, during the first months of the pandemic, food insecurity showed marked socio-spatial differences. The most affected households were those where children and adolescents lived. The analysis at departmental level confirms this trend and reveals critical areas of food insecurity and perception of hunger associated with conditions of persistent inequality. The results and cartographic developments obtained provide evidence on the vulnerability of child populations in the context of a pandemic.